Peningkatan Kemampuan majanemen Keuangan Individu Masyarakat Desa Cijurey Melalui Literasi Keuangan dan Literasi Digital - Mulyani, Hani Sri (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid development of financial technology (fintech) in Indonesia has made it easier for people to access various digital financial services. However, low levels of digital financial literacy remain a major challenge in achieving sustainable financial inclusion. The imbalance between increasing financial inclusion and financial literacy has resulted in many people having access to financial products without understanding how to use them wisely, leaving them vulnerable to risks such as illegal online loans, fraudulent investments, digital fraud, and consumptive behavior. This situation highlights the need to strengthen the community's financial management skills by simultaneously improving financial literacy and digital literacy. This community service activity, conducted in Cijurey Village, Panyingkiran District, aims to improve the community's ability to manage personal and household finances through the integration of financial literacy and digital literacy. The approach used is community-based learning, through face-to-face training that is participatory, contextual, and applicable. Participants are equipped with an understanding of financial planning, the safe use of financial technology, and hands-on practice in digital financial management. The integration of these two literacy skills is expected to shape smart, critical, and adaptive financial behavior to the development of the digital economy, while strengthening the community's financial management capacity towards sustainable economic prosperity.